Determinan Health- Related Quality of Life Pasien Terapi Hemodialysis dengan Instrument EQ5D-5L - Estuningtyas Ayu Hapsari; sutiyono; Gigih Kenanga Sari (Universitas An Nuur, 2023)
Background: Chronic kidney disease is caused by an increase in serum creatinine values of 20% in the kidneys. One of the management therapies for chronic kidney disease is hemodialysis therapy. The EQ5D-5L instrument is an instrument that can be used to measure the quality of chronic kidney patients. The aim of the study was to determine the description of patients with hemodialysis therapy and determine the response of patients to hemodialysis therapy with EQ5D-5L. Method: The research method is quantitative descriptive. Data collection used the EQ5D-5L instrument with the inclusion criteria of patients diagnosed with chronic kidney disease in patients aged more than 19 years. Sampling using the accidental sampling method was 100 respondents. Data analysis uses univariate analysis determinants. Results: The results of the study showed that patients with the highest range were aged 45-64 with a percentage of 67%, the proportion of male had the highest value with a percentage of 63%, the highest CCI value was in the range 3-4 with a percentage of 44% and the most therapy implementation was less than 1 year of therapy with a percentage of 59%. The utility measurement results showed that the EQ5D-5L average value was 0.595 and the VAS average value was 80, for the EQ5D-5L SD value was 0.225 and the VAS SD value was 6.464, with the EQ5D-5L median value being 0.624 and the VAS median value being 80. The most dominant response was pain at 75% and anxiety at 62%. Conclusion: Conclusion. The results of the study showed that the age of hemolysis therapy was highest in men with an average EQ5D-5L utility value of 0.595 and an average VAS value of 80. The most dominant response was pain at 75% and anxiety at 62%